Dynamic and Static Characteristics of Wavy Annular Seals in Turbulent Flow - Satyam Shivam Gautam (Japanese Society of Tribologists, 2010)
This paper presents results of a theoretical analysis to determine the leakage flow and dynamic characteristics of circumferential wave geometry annular seals using turbulent lubrication theory. Turbulent lubrication equations based on an eddy viscosity model have been used to develop the turbulent Reynolds equation. Convective fluid inertia effects have been incorporated using the perturbation approach in turbulent lubrication. To determine the dynamic characteristics i.e. stiffness, damping and whirl ratio, perturbation theory for small amplitude vibration of the journal center has been adopted. In general, it has been found that circumferential wave geometry improves the performance of the annular seal at higher speeds and increases in the L/D and taper ratios.